Long-term survival analysis of HIV patients receiving antiretroviral treatment in Congo: a 14-year retrospective analysis, 2003–2017 - Gilbert Ndziessi; Ange Clauvel Niama; Arkadit Jeandria Nkodia; Merlin Diafouka (AIDS Research and Therapy, 2026)
Abstract Background Long-term survival of people living with HIV (PLHIV) on antiretroviral therapy (ART) is poorly documented in the Republic of Congo. Methods We conducted a retrospective cohort study of 2,309 adults initiating ART between 2003 and 2017. Survival was estimated using the Kaplan-Meier method, and determinants were assessed using Cox regression. Results The median age of participants was 49 years (IQR 42–57), and women represented 68.6% of the cohort. The 14-year overall survival probability was 83% (95% confidence interval: 78–87). The overall incidence rate of mortality was 1.01 per 100 person-years (95% CI: 0.88–1.16). Stratified by sex, incidence was higher among men (1.43 per 100 PY; 95% CI: 1.15–1.75) compared to women (0.82 per 100 PY; 95% CI: 0.68–0.98). In multivariable time-dependent analysis, male sex (adjusted hazard ratio [AHR] = 1.66; 95% CI: 1.26–2.19), baseline viral load > 1000 copies/ml (AHR = 2.53; 95% CI: 1.92–3.35), and WHO clinical stage (AHR = 2.70; 95% CI: 1.94–3.77) were independently associated with mortality. The time-dependent effect of WHO stage was not statistically significant, indicating stable hazard ratios over time. The final model demonstrated excellent discrimination (AUC = 0.901) and satisfied the proportional hazards assumption. Conclusion Suboptimal survival and increased mortality were mainly driven by presentation with advanced HIV disease and were strongly associated with high viral load and male sex, underscoring persistent gaps in early HIV diagnosis, timely ART initiation, and strengthened viral load monitoring.